Towards the use of Policy Decomposition for Composite Service Management by Non-expert End-users - KEENEY, JOHN; LEWIS, DAVID; WADE, VINCENT PATRICK (My University, 2010)
With the advent of Web 2.0, as web service composition gets easier, there is a trend towards nonexpert users not just consuming information and services, but also providing, aggregating, composing and eventually managing their own information, services and resources. However non-expert users need to manage their composed services in a way they can understand. Policy-based management promises the ability to control services in a consistent manner via high-level declarative directives, constraints and goals. However, a significant drawback of policy-based management for complex systems remains the lack of an automated mechanism to resolve the meaning of high-level goals so they can be enforced.
IFIP/IEEE International Workshop on Business-driven IT Management
PUBLISHED
Osaka, Japan
Keywords: Computer Science